The Effectiveness of Inquiry Learning Method with Ethnomathematics Approach on Students' Mathematical Understanding Grade VII SMPN 1 Bringin - Luki Rahmawati; Arum Dwi Rahmawati; Budi Sasomo (Institute of Educational, Research, and Community Service, 2024)
This research aims to determine the effectiveness of the inquiry learning method with an ethnomathematics approach on the mathematical understanding of class VII students at SMPN 1 Bringin for the 2023/2024 academic year. The method used in this research is a quantitative method with a quasi-experimental research design. With research subjects from class VII, 56 students were taken from the experimental class and 56 students from the control class. Data collection was carried out by means of a post-test carried out at the end of the lesson which was used to determine students' mathematical understanding. In analyzing the data, this research uses statistical data analysis with a formula (t test). The research results show a significant difference with a calculated t value = 2.199 and t table = 2.056 with a significance level of 0.05. The average score of students after being taught using the inquiry learning method with an ethnomathematics approach was 93,50, while the average score of students using the direct learning model was 87,93. Thus, the use of the inquiry learning method with an ethnomathematics approach is effective in the mathematical understanding of class VII students at SMPN 1 Bringin for the 2024/2025 academic year.